VISUAL OUTCOMES WITH INTRAOCULAR TRIFOCAL LENS IMPLANT - Sarfaraz, Sana Ahmed; Muhammad Ali Haider ,; Hussain Ahmed Khaqan,; Nida Usman,; Arslan Ahmed,; Uzma Sattar,; Hasnain Muhammad Buksh,; Rahila Ikram, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Cataract surgery has become one of the most common surgeries in the world with one in every four surgeries performed being a cataract extraction and the numbers are expected to increase by 16 percent in the USA alone by 2024 as compared to the current statistics. The aim of the study is to analyze the visual outcomes of intraocular lens implants for various visual ranges. Methods: This non-comparative interventional study was conducted at the Ophthalmology department of Al Ehsan Eye Hospital from Jan to Dec 2021. It included patients who underwent uneventful phacoemulsification with an intraocular lens implant and analysis of the visual outcomes for uncorrected distance (UDVA), uncorrected intermediate distance (UIVA), and uncorrected near distance (UNVA). Results: Independent sample t-test was applied to observe the mean values of recorded far vision on the 1stday, 1 week, and 1 month after the trifocal intraocular lens implantation. It showed a significant difference with a p-value of 0.00 on 1st day, 1 week, and 1 month after was 0.3±0.1, 0.17±0.09, and 0.14±0.08 respectively. Mean improvement in near vision after 1 month was N6 with S.D 1.03 and in intermediate vision was N8±1.4 respectively. Conclusion: Trifocal Intraocular lens implantation offers an improved vision for near, intermediate, and distant visual ranges without the need for correction.